Life history and population growth parameters of the astigmatid mite Histiostoma feroniarum (Acari: Histiostomatidae) feeding on Fusarium graminearum - Forough Bahrami; Yaghoub Fathipour; Karim Kamali (Persian Journal of Acarology)
In this study, the life history and demographic parameters of Histiostoma feroniarum (Defour) on Fusarium graminearum Clade were studied under laboratory condition. The incubation, larval and nymphal periods and longevity of adults were observed to be 1.6, 2.56, 3.09 and 10.48 days, respectively. The sex ratio was 0.65. Pre-oviposition, oviposition and post-oviposition periods lasted 1.8, 8.27 and 0.66 days, respectively. The gross reproductive rate (GRR), net reproductive rate (R0), intrinsic rate of increase (rm), finite rate of increase (λ), mean generation time (T) and doubling time (DT) were calculated to be 110.56 females/female, 23.54 females/ female, 0.195 day-1, 1.215 day-1, 16.23 days and 3.55 days, respectively. The results of this study reveal high potential of H. feroniarum as a major pest of laboratory cultures.